Effects‐driven chemical fractionation of heavy fuel oil to isolate compounds toxic to trout embryos. (18th February 2014) - Bornstein, Jason M.; Adams, Julie; Hollebone, Bruce; King, Thomas; Hodson, Peter V.; Brown, R. Stephen
Abstract Heavy fuel oil (HFO) spills account for approximately 60% of ship–source oil spills and are up to 50 times more toxic than medium and light crude oils. Heavy fuel oils contain elevated concentrations of polycyclic aromatic hydrocarbons (PAHs) and alkyl‐PAHs, known to be toxic to fish; however, little direct characterization of HFO toxicity has been reported. An effects‐driven chemical fractionation was conducted on HFO 7102 to separate compounds with similar chemical and physical properties, including toxicity, to isolate the groups of compounds most toxic to trout embryos. After each separation, toxicity tests directed the next phase of fractionation, and gas chromatography–mass spectrometry analysis correlated composition with toxicity, with a focus on PAHs. Low‐temperature vacuum distillation permitted the separation of HFO into 3 fractions based on boiling point ranges. The most toxic of these fractions underwent wax precipitation to remove long‐chain n‐alkanes. The remaining PAH‐rich extract was further separated using open column chromatography, which provided distinct fractions that were grouped according to increasing aromatic ring count. The most toxic of these fractions was richest in PAHs and alkyl‐PAHs. The results of the present study were consistent with previous crude oil studies that identified PAH‐rich fractions as the most toxic. Environ Toxicol Chem 2014;33:814–824. © 2013 SETAC